A Recent Achievement In the Discovery and Development of Novel Targets for the Treatment of Type-2 Diabetes Mellitus - Belete TM (Dove Medical Press, 2020)
Tafere Mulaw Belete Department of Pharmacology, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Tafere Mulaw Belete Tel +251 918045943Email mutafere@yahoo.comAbstract: Type 2 diabetes (T2DM) is a chronic metabolic disorder. Impaired insulin secretion, enhanced hepatic glucose production, and suppressed peripheral glucose use are the main defects responsible for developing the disease. Besides, the pathophysiology of T2DM also includes enhanced glucagon secretion, decreased incretin secretion, increased renal glucose reabsorption, and adipocyte, and brain insulin resistance. The increasing prevalence of T2DM in the world beseeches an urgent need for better treatment options. The antidiabetic drugs focus on control of blood glucose concentration, but the future treatment goal is to delay disease progression and treatment failure, which causes poorer glycemic regulation. Recent treatment approaches target on several novel pathophysiological defects present in T2DM. Some of the promising novel targets being under clinical development include those that increase insulin sensitization (antagonists of glucocorticoids receptor), decreasing hepatic glucose production (glucagon receptor antagonist, inhibitors of glycogen phosphorylase and fructose-1,6-biphosphatase). This review summarizes studies that are available on novel targets being studied to treat T2DM with an emphasis on the small molecule drug design. The experience gathered from earlier studies and knowledge of T2DM pathways can guide the anti-diabetic drug development toward the discovery of drugs essential to treat T2DM.Keywords: Type-II diabetes mellitus, antihyperglycemic, insulin resistance, novel drug target